2002
DOI: 10.1046/j.0953-816x.2001.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential subcellular localization of the 5‐HT3‐As receptor subunit in the rat central nervous system

Abstract: Following the cloning and sequencing of the A subunit of the 5-HT3 receptor, two alternatively spliced isoforms, 5-HT3-AS and 5-HT3-AL, have been identified. In order to analyse the distribution of the receptor, a polyclonal antibody has been produced against the short form which is the most abundant in the central nervous system [Doucet et al. (2000) Neuroscience 95, 881-892]. As expected from the recognition of functional 5-HT3 receptors, immunostaining by this anti-5-HT3-R-AS antibody matched the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 51 publications
3
70
0
Order By: Relevance
“…This putative sensory modulation role is consistent with the presence of 5-HT receptors in the dorsal horn of the lumbosacral spinal cord (Liu et al, 2002). Furthermore, numerous findings associate 5-HT with sensory input modulation (Machacek et al, 2001;Meuser et al, 2002;Miquel et al, 2002;Shay and Hochman, 2002;Bosco et al, 2003;Hains et al, 2003). In intact cats, monoamine release selectively increases the excitability of some reflex circuits but decreases the excitability of others, e.g., potentiating transmission from group I spindle fibers and tendon organs (Edgley et al, 1988;Bras et al, 1990) while depressing transmission from nociceptors and group II fibers (Headley et al, 1978; Figure 5.…”
Section: Discussionsupporting
confidence: 58%
“…This putative sensory modulation role is consistent with the presence of 5-HT receptors in the dorsal horn of the lumbosacral spinal cord (Liu et al, 2002). Furthermore, numerous findings associate 5-HT with sensory input modulation (Machacek et al, 2001;Meuser et al, 2002;Miquel et al, 2002;Shay and Hochman, 2002;Bosco et al, 2003;Hains et al, 2003). In intact cats, monoamine release selectively increases the excitability of some reflex circuits but decreases the excitability of others, e.g., potentiating transmission from group I spindle fibers and tendon organs (Edgley et al, 1988;Bras et al, 1990) while depressing transmission from nociceptors and group II fibers (Headley et al, 1978; Figure 5.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, in many brain regions 5-HT 3 receptor-bearing neurons do not receive synaptic serotonergic innervation and serotonergic axons often do not form classical synapses (Descarries et al, 1990;Umbriaco et al, 1995), implying volume transmission as the predominant way by which serotonin exerts its function. There is also ample evidence for the existence of presynaptic 5-HT 3 receptors in different brain areas (Nichols and Mollard, 1996;Nayak et al, 1999;Miquel et al, 2002), and functional analyses demonstrated that presynaptic 5-HT 3 receptors can regulate GABA release (Ropert and Guy, 1991;Glaum et al, 1992;Koyama et al, 2000;Katsurabayashi et al, 2003;Turner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The conjugation of synthetic peptides to protein carriers may create three-dimensional conformations of peptides that mimic those seen in fixed neural tissue, but may also lead to the disappearance of particular antigenic determinants. It is possible, therefore, that these differences in the preparation of the antigen might result in epitopes with distinct molecular configurations, which could produce antibodies that recognize distinct conformations of the 5-HT 2A receptor protein located in different neuronal domains, similar to the situation with different 5-HT 3R antibodies (Morales et al, 1998;Miquel et al 2002). It is also possible that these antibodies might recognize different post-translational modifications of the receptor proteins, as has been shown for different 5-HT 1A R antibodies (Anthony and Azmitia, 1997).…”
Section: Staining Differences Exhibited By the 5-ht 2a R Antibodiesmentioning
confidence: 99%